Using scenario planning to assess governance reforms for enhancing biodiversity outcomes. (January 2016) - Mitchell, Michael; Lockwood, Michael; Moore, Susan A.; Clement, Sarah; Gilfedder, Louise; Anderson, Gill
Highlights: We use a modified scenario planning process to test efficacy of governance reforms. We engaged biodiversity stakeholders from two landscapes for this assessment. More formal governance options were preferred over those involving devolution. While challenging, participants appreciated the logical staged workshop process. The process we trialled is well suited to action research applications. Abstract: Governance arrangements frame and direct how land managers respond to the multiple demands and challenges of conserving biodiversity. Biodiversity conservation requires attention to how social-ecological systems (SES) change and can be influenced over time. It is important that governance settings within these systems can support achievement of biodiversity outcomes. Two questions then arise. Will current arrangements lead to desirable biodiversity outcomes, and if not, are there other arrangements that plausibly might do better? However, methods for answering these questions in collaboration with critical stakeholders such as policy makers and land managers are not evident in the literature. The aim of this paper is to explore the use of a participatory scenario planning process to test the efficacy of proposed governance reforms for enhancing biodiversity outcomes in two contrasting landscapes in Australia. A workshop process was used to consider the effect of the reform options on key drivers of change, and thus how these affected drivers would in turn modify future scenarios, and the biodiversity outcomes of these scenarios. In both landscapes, there was a preference for reforms that retained governmental influence or control, in contrast to academic calls for adaptive governance that emphasises the importance of self-organisation and devolution of authority. The workshop process, although complex and cognitively challenging, was regarded by participants as suitable for testing the utility of alternative governance options for biodiversity conservation. Challenges for the future include designing and considering reforms based on what is possible rather than probable or preferable, and engaging participants over time to build knowledge, engagement and trust. The paper concludes with suggestions for addressing these challenges.